2020
DOI: 10.1111/ejh.13370
|View full text |Cite
|
Sign up to set email alerts
|

Use of eltrombopag for patients 65 years old or older with immune thrombocytopenia

Abstract: Background Eltrombopag is useful for immune thrombocytopenia (ITP). However, results of clinical trials may not accurately mirror clinical practice reality. Here we evaluated eltrombopag for primary and secondary ITP in our ≥65‐year‐old population. Methods A total of 106 primary ITP patients (16 with newly diagnosed ITP, 16 with persistent ITP, and 74 with chronic ITP) and 39 secondary ITP patients (20 with ITP secondary to immune disorders, 7 with ITP secondary to infectious diseases, and 12 with ITP secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…It may be primary or secondary to an underlying disorder – infections, autoimmune diseases, cancer or medications. [ 4 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…It may be primary or secondary to an underlying disorder – infections, autoimmune diseases, cancer or medications. [ 4 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that TPO-RA efficacy is similar in older and younger patients. 47 , 48 , 81 Although the overall tolerance of TPO-RA is good, there are some concerns about long- and short-term adverse events. The risk of reticulin deposits in bone marrow has been raised in patients with long-term use of TPO-RAs but does not lead to bone-marrow failure and is reversible after drug discontinuation.…”
Section: Itp Treatments: What Tolerance and What Efficacy In Older Pa...mentioning
confidence: 99%
“…It provides many advantages over other drugs, especially in the elderly population. Comorbidities related to old age affect the course of the disease and responses to treatment (10). Treatment of chronic ITP is difficult, especially because of limited resources and treatment-related complications (11).…”
Section: Introductionmentioning
confidence: 99%